(untitled) (Fiep Bulletin - online, 2010)
Currently there are several methods of teaching in physical education in present practice, which clearly signals the need for constant reflection and debate on the ongoing academic training in order to achieve a significant relevance in the context of developing the learning process. Within this context we have initial main objective of this study provide a reflection on teaching in physical education, in view of the academic learning process developed in university courses in Physical Education. We used to meet the objectives proposed a qualitative study in the literature that we seek the components necessary for the consolidation of reflection. Ignore the common knowledge and experiences of all stakeholders in the school environment, especially the students, the idea seems common in training courses in Physical Education, for this, the overwhelming majority favor the education focused on determining who has the unilateral figure teacher the main actor in / of the learning process. Where knowledge is constructed collectively and reflective nature, all become in this participatory process, in a manner that allows comparisons and relations of knowledge to empower and enable a knowledge of the dialogic nature and landscape.